Fusion power predictions for βN ≈ 1.8 baseline scenario with 50–50 D–T fuel mix and NBI injection in preparation to D–T operations at JET. (1st July 2022) - Zotta, V.K.; Garzotti, L.; Casson, F.J.; Frigione, D.; Köchl, F.; Lerche, E.; Lomas, P.; Rimini, F.; Sertoli, M.; Van Eester, D.; Gatto, R.; Mazzotta, C.; et al.
Abstract: The fusion performance of ELMy H-mode 50–50 deuterium–tritium (DT) plasmas with 50–50 DT NBI injection and q 95 ≈ 3 and β N ≈ 1.8 (also referred to as medium- β N baseline scenario in the rest of this paper) are predicted with the JINTRAC suite of codes and the QuaLiKiZ transport model. The predictions are based on the analysis of plasmas from the first DT campaign on JET in 1997 (DTE1) and pure deuterium plasmas developed at JET in preparation for the DT experimental campaign in 2021 (DTE2), after the installation of a Be/W ITER-like wall in 2011. The sensitivity of the predictions to plasma parameters such as current, toroidal field, pedestal confinement and impurity content are analysed together with the sensitivity to the amount of auxiliary heating power available. The simulations indicate that a fusion power of 10 MW should be achievable under a fairly wide range of assumptions, provided that the auxiliary heating power is around or above 38 MW. Higher fusion power approaching 15 MW could be achievable for this value of β N only for particularly pure plasmas and with 40 MW of additional heating power.